Pendampingan dalam Mengatasi Disleksia pada Anak Indonesia di Malaysia dengan Metode Team Teaching - Sifa Yunita Sari; Erie Hariyanto; Moch. Cholid Wardi; Moh. Hamzah; Muhamad Habibullah (Universitas Sebelas Maret, 2025)
Indonesian children in Malaysia who come from migrant families often face limited access to education, including in dealing with learning difficulties such as dyslexia. This community service activity aims to assist children with dyslexia through the application of the team teaching method in an informal learning environment. The implementation method is carried out in a collaborative participatory manner by involving teachers and volunteers as the main facilitators in the learning process. The program is implemented in three stages: team teaching method training, classroom learning assistance, and evaluation of child development. The results of the activity show that this approach is able to create a more interactive and focused learning atmosphere, improve basic reading skills, and build children's self-confidence. Teachers also feel the benefits of dividing roles in managing the class and adjusting learning strategies more effectively. Parental involvement is limited, but does not hinder the course of the activity. This community service suggests the team teaching method as an effective learning strategy for migrant children with special learning needs, especially dyslexia, in the context of informal education.Anak-anak Indonesia di Malaysia yang berasal dari keluarga migran sering menghadapi keterbatasan akses pendidikan, termasuk dalam menangani kesulitan belajar seperti disleksia. Kegiatan pengabdian ini bertujuan untuk mendampingi anak-anak dengan disleksia melalui penerapan metode team teaching di lingkungan belajar informal. Metode pelaksanaan dilakukan secara partisipatif kolaboratif dengan melibatkan guru dan relawan sebagai fasilitator utama dalam proses pembelajaran. Program dilaksanakan dalam tiga tahap: pelatihan metode team teaching, pendampingan belajar di kelas, serta evaluasi perkembangan anak. Hasil kegiatan menunjukkan bahwa pendekatan ini mampu menciptakan suasana belajar yang lebih interaktif dan terfokus, meningkatkan kemampuan membaca dasar, serta membangun kepercayaan diri anak. Guru juga merasakan manfaat dari pembagian peran dalam mengelola kelas dan menyesuaikan strategi belajar secara lebih efektif. Keterlibatan orang tua bersifat terbatas, namun tidak menghambat jalannya kegiatan. Pengabdian ini menyarankan metode team teaching sebagai strategi pembelajaran yang efektif untuk anak-anak migran dengan kebutuhan belajar khusus, khususnya disleksia, dalam konteks pendidikan informal.